Wong Solo Community Alternative Practical Strategy in Optimizing the Performance of the Intelkam Unit Carrying Out Early Detection of Radical Intelligence and Terrorism Networks in the Jurisdiction of the Surakarta Police - Brimtedo, Reyhan (Indonesian Journal of Police Studies, 2024)
The number of cases of terrorist arrests in the city of Surakarta is increasing, at least almost every year there have been activities of arrests of terror suspects and suspects since 2004. Radical understanding is very dangerous because it can cause danger anytime anywhere in any way. So that pre-emptive action is needed by members of the Indonesian National Police. Many factors influence the implementation of early detection, but these obstacles are assisted by the strength and potential of the Surakarta Police Intelligence Unit. The main threat is the existence of ex-convicts and various educational or religious institutions that involve the younger generation and women in spreading radical views and even involving them in acts of terrorism. Retrieval of data in this study through observation, interviews and study of documents. The results in this study found that early detection activities carried out by the Surakarta Police intelligence unit were not optimal so that cooperation with the community and other functional units as well as external partners.